Characteristics and performance of SA most empowered companies - Ndlangamandla, Phiwokwakhe Kenneth (My University, 2017)
The purpose of the study was to understand the characteristics of SA highly empowered companies and investigate the main factors influencing performance and survival of those BEE companies. The present study mainly based on secondary data. This study uses data supplied by Empowerdex financial consultants firm, for the SA BEE most empowered companies from 2004 (during the inception of the codes of goods practise) through to 2016. The performance was measured by return on total assets as a dependent financial performance variable. The return on equity, profit margin, earnings per share, price earnings, share price, and BEE score are used as independent variables, which are proxies for profitability, market, and BEE score. Descriptive and inferential analysis has been performed using the Statistical Package for the Social Sciences (SPSS) version 24 tool for Quantitative analysis. Pearson correlation and Regression test are employed to determine the kind of relationship between dependent and independent variables, hypotheses test and evaluating normality of data respectively. In order to test multiple linear regression models, the researcher assessed the study data collected through four assumption tests; these tests include normality test, multicollinearity test, autocorrelation test and heteroscedasticity. Based on findings of the study, regarding financial ratio analysis approach, the study concluded that there is a high share price. This pattern reveals that BEE empowered companies in South Africa rank SP higher than other performance measurement indicators. While regarding the statistical analysis it can be concluded that there is a strong and significant relationship between return on assets (ROA) with (profitability measures) ROE, PM and EPS. Results further show that there is a significant strong positive correlation between ROE and ROA with a significant value of 0.000, while there is a positive and significant relationship between PM and ROA. Results show that there is a significant strong positive correlation between EPS and ROA. The correlation coefficient for EPS and ROA is 0.157 with a statistically significant correlation value of 0.003. That means, increases or decreases in one variable do significantly relate to increases or decreases in your second variable. There is a negative correlation between ROA and market value. There is an insignificant and negative correlation between P/E and ROA. Data also shows that there is an insignificant and negative correlation between SP and ROA Data further indicate that there is a significant strong negative correlation between ROA and BEE score with a significant value of 0.001. There is a statistically significant correlation between BEE score and ROA. That means, increases or decreases in one variable do significantly relate to increases or decreases in your second variable. SPSS generated a negative Pearson’s r value, meaning that when the amount of BEE score increases (our first variable), and the ROA (our second variable) decreases. The p-value for this correlation coefficient is 0.001. In conclusion, BEE score has a negative relationship with the return on assets.
A research report submitted to the Faculty of Commerce, Law and Management, in partial fulfilment of the requirements for the degree of Master of Management in Finance and Investment, University of the Witwatersrand, Johannesburg, 2017
Keywords: Employee empowerment--South Africa; Blacks--Empowerment--South Africa